2007
DOI: 10.1162/jocn.2007.19.10.1690
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Onset Relational Memory Effects Are Evident in Eye Movement Behavior, but Not in Hippocampal Amnesia

Abstract: Little is known about the mechanisms by which memory for relations is accomplished, or about the time course of the critical processes. Here, eye movement measures were used to examine the time course of subjects' access to and use of relational memory. In four experiments, participants studied faces superimposed on scenic backgrounds and were tested with three-face displays superimposed on the scenes viewed earlier. Participants exhibited disproportionate viewing of the face originally studied with the scene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
316
5
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(364 citation statements)
references
References 53 publications
41
316
5
2
Order By: Relevance
“…On each test trial, a studied scene was shown, and after a delay, a test display consisting of the scene and three previously studied faces was presented. Consistent with previous studies using a similar paradigm (Hannula et al, 2007), participants tended to disproportionately look at the face that was previously paired with the scene, suggesting that eye movements were influenced by the previously learned face-scene association. Activity in the hippocampus and PRc during initial presentation of the scene was predictive of the extent to which participants subsequently viewed the correct face, even when they failed to explicitly recognize it as the associate (Fig.…”
Section: The Mtl Is Not the Site Of Conscious Recollectionsupporting
confidence: 87%
“…On each test trial, a studied scene was shown, and after a delay, a test display consisting of the scene and three previously studied faces was presented. Consistent with previous studies using a similar paradigm (Hannula et al, 2007), participants tended to disproportionately look at the face that was previously paired with the scene, suggesting that eye movements were influenced by the previously learned face-scene association. Activity in the hippocampus and PRc during initial presentation of the scene was predictive of the extent to which participants subsequently viewed the correct face, even when they failed to explicitly recognize it as the associate (Fig.…”
Section: The Mtl Is Not the Site Of Conscious Recollectionsupporting
confidence: 87%
“…Representations maintained in memory can affect, and be affected by, gaze fixation patterns (Loftus, 1972;Ryan and Cohen, 2004;Henderson et al, 2005;Holm and Män-tylä, 2007;Castelhano et al, 2009;Foulsham and Kingstone, 2013;. Studies with older adults and neuropsychological cases have found altered fixation patterns that may be functionally linked to these participants' memory deficits (Ryan et al, 2000;Hannula et al, 2007;Chan et al, 2011;Voss et al, 2011;Shih et al, 2012;Rondina et al, 2016a). Neuroimaging studies also show that hippocampal responses are predictive of (or aligned with) eye movement patterns that express memory retrieval (Hannula and Ranganath, 2009;Ryals et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is thought to index or bind parsed information from neocortical regions to form vivid associative, relational, or episodic memories (Teyler and DiScenna, 1986;Davachi, 2006;Squire et al, 2007;Teyler and Rudy, 2007;Eichenbaum and Cohen, 2014;Moscovitch et al, 2016) and is particularly sensitive to novel information processing (Kumaran and Maguire, 2007, Suzuki et al, 2011a, 2011bVannini et al, 2013;Kremers et al, 2014). The hippocampus has been implicated for its role in guiding where to look during memory retrieval (Ryan et al, 2000;Hannula et al, 2007Hannula et al, , 2012Ryals et al, 2015), but no human neuroimaging study has yet examined directly the relationship between hippocampal activity and visual sampling behavior during encoding.…”
Section: Introductionmentioning
confidence: 99%
“…However, such eye movement indices of memory are not present in certain populations, such as when healthy older adults and patients with amnesia due to medial temporal lobe damage are assessed for their memory of the spatial relations among objects in scenes, as outlined in Figure 3 2,8 . Therefore, findings from eye movement monitoring can be used to contrast memory among groups of participants with differing neuropsychological status [2][3][8][9][10] . Figure 2.…”
Section: Figure 1 Example Of a Head-mounted Video-based Eye Tracker mentioning
confidence: 99%
“…Memory can also be interrogated for its specificity; for instance, eye movement patterns that differ between an identical and an altered version of a previously studied image reveal the storage of the altered detail in memory 2-3, 6-8 . These indices of memory can be compared across participant populations, thereby providing a powerful tool by which to examine the organization of memory in healthy individuals, and the specific changes that occur to memory with neurological insult or decline [2][3][8][9][10] . …”
mentioning
confidence: 99%